Polar education and storytelling: the narratives of the "Antarctica Cases" (PerCursos, 2022)
Antarctica is a relevant continent to be studied. However, it is often laden with myths and misinformation about it. Thus, Digital Storytelling (DST) about Antarctica can collaborate with the teaching-learning process, since it is necessary to seek data for the plot’s development. Therefore, the objectives of this research are (i) to present the methodology for creating an extension course on Antarctica, in a totally remote way; (ii) to describe the content of the videos produced – called Cases of Antarctica; and (iii) to analyze the Antarctic Cases, prepared by the students, with the DST method. The extension course was developed in four synchronous meetings, with the participation of 25 students. To carry out the proposal, audiovisual and theoretical material and content review games were organized. The creation of Antarctica Cases by the participants occurred asynchronously. The stories presented by the participants involved physical aspects of the continent, the local fauna, migratory aspects and cartographic concepts, items worked during the course Cases of Antarctica. The success of the method adopted stands out, although remote teaching, with its overload of activities, made it impossible for most participants to complete the course. Finally, the course provided the knowledge construction by the participants, who became able to contribute with experiences and memories that will be used in their teaching career and aimed at the realization of polar teaching in schools.
Keywords: Antarctica; polar teaching; remote teaching